The Potential Role of Awe for Depression: Reassembling the Puzzle - Chirico, Alice; Gaggioli, Andrea (Frontiers in Psychology, 2021)
Recently, interest in the unique pathways linking discrete positive emotions to specific health outcomes has gained increasing attention, but the role of awe has yet to be elucidated. Awe is a complex and transformative emotion that restructures individuals’ mental frames so deeply that it could be considered a therapeutic asset for major mental health major issues, including depression. Despite sparse evidence showing a potential connection between depression and awe, this link has not been combined into a proposal resulting in specific intervention guidelines. The aim of this perspective was threefold: (i) to provide a new unifying model of awe’s functioning – the Matryoshka model; (ii) to show systematic and explicit connections between this emotion and depression; and (iii) to suggest specific guidelines of intervention utilizing the potential therapeutic role of awe for mental health, specifically for depression. This theoretical endeavor in its entirety has been framed within the health domain.